Do media reports reflect the real threats to wildlife? - Morini, Rúbia Ferreira dos Santos; Ribeiro, Rullian César [UNESP]; Trentini, Isabela Pivetta; Sandoval, Eluzai Dinai Pinto [UNESP]; Silva, Amanda Rosa da [UNESP]; Oliveira, Márcio Leite de (Elsevier, 2023)
The media generates public consensus, acting as a driver of public policies. In the Anthropocene biodiversity crisis, the role of the media is critical in generating public engagement on conservation public policies. In this study, we aimed to compare the frequency of threats to deer species in media reports with the threats' relevance indicated by experts in the IUCN assessments. For this purpose, we created a ranking of threats importance based on IUCN assessments. In addition, we created a ranking of threats frequency on reports from media, obtained through the “news” tool from Google from 2011 to 2021. We compared both rankings with a kappa agreement test and found different levels of agreement from non-significant agreement to moderate to high agreement, according to the taxonomic group analyzed. With some exceptions, we were able to observe that the main threats described at IUCN assessments coincide with what is reported by the media. However, threats associated with diseases, low reproductive efficiency and population sustainability are underreported. As these threats are somehow invisible to the general public, it may lead to deficiencies in conservation actions that prevent or mitigate the impact of epidemics, inbreeding depression and genetic drift. These specific gaps between the rankings should be the focus of future conservation science popularization activities and cooperation between academics and journalists.
Keywords: Conservation; Deer; Neotropical; Newspaper; Press; Public opinion